OsOLP1 contributes to drought tolerance in rice by regulating ABA biosynthesis and lignin accumulation - Yan, Jianpei; Ninkuu, Vincent; Fu, Zhenchao; Yang, Tengfeng; Ren, Jie; Li, Guangyue; Yang, Xiufen; Zeng, Hongmei (Frontiers in Plant Science, 2023)
Global rice consumption has consistently increased with the increasing population. Over 510 million metric tons of rice were consumed in the 2021/2022 season, representing an increase of over 10,000 metric tons from the previous year. There is an urgent need to enhance rice drought tolerance in the face of the unwavering depletion of terrestrial water due to climate change to meet the world's rice demand. Osmotin-like proteins promote plant resistance to biotic and abiotic stresses. However, the mechanism of drought aversion by osmotin-like proteins in rice remains unclear. This study identified a novel osmotin-like protein, OsOLP1, that conforms to the structure and characteristics of osmotin family and is induced by drought and NaCl stress. To elucidate the function of OsOLP1 in rice drought tolerance, we generated OsOLP1 overexpression lines and CRISPR/Cas9-mediated knockout lines. Compared to wild-type plants, transgenic rice plants overexpressing OsOLP1 showed high drought tolerance with leaf water content of up to 65%, and a survival rate of 53.1% by regulating 96% stomatal closure and more than 2.5-fold proline content promotion through the accumulation of 1.5-fold endogenous ABA, and enhancing about 50% lignin synthesis. However, OsOLP1 knockout lines showed severely reduced ABA content, decreased lignin deposition, and weakened drought tolerance, indicating that OsOLP1 contributes to drought tolerance in rice. These results provide new insights into our perspective on rice drought tolerance.